2015
DOI: 10.1172/jci80743
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of mutant huntingtin protein in cerebrospinal fluid from Huntington’s disease patients

Abstract: BACKGROUND:Quantification of disease-associated proteins in the cerebrospinal fluid (CSF) has been critical for the study and treatment of several neurodegenerative disorders; however, mutant huntingtin protein (mHTT), the cause of Huntington's disease (HD), is at very low levels in CSF and, to our knowledge, has never been measured previously. METHODS:We developed an ultrasensitive single-molecule counting (SMC) mHTT immunoassay that was used to quantify mHTT levels in CSF samples from individuals bearing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
236
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 221 publications
(259 citation statements)
references
References 32 publications
14
236
4
1
Order By: Relevance
“…We were able to analyse in detail the associations with NfL from before disease onset and during manifest disease supported by rigorous clinical, cognitive, and neuroimaging data. Additionally, we were able to replicate the principal plasma findings in an independent cohort and confirm that concentrations in CSF are increased in individuals with HTT mutations, as has been previously reported 8, 9, 15, 16, 17. We further showed that NfL concentrations in plasma and CSF are closely correlated, which affirms the likely CNS origin of the NfL detected in both biofluids and suggests that NfL in blood could be a reliable estimator of concentrations in CSF.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We were able to analyse in detail the associations with NfL from before disease onset and during manifest disease supported by rigorous clinical, cognitive, and neuroimaging data. Additionally, we were able to replicate the principal plasma findings in an independent cohort and confirm that concentrations in CSF are increased in individuals with HTT mutations, as has been previously reported 8, 9, 15, 16, 17. We further showed that NfL concentrations in plasma and CSF are closely correlated, which affirms the likely CNS origin of the NfL detected in both biofluids and suggests that NfL in blood could be a reliable estimator of concentrations in CSF.…”
Section: Discussionsupporting
confidence: 87%
“…Many potential markers in CSF have been proposed, but only a few (eg, mHTT itself, microtubule-associated protein tau, and chitinase-3-like protein 1) have shown associations with clinical phenotype beyond established predictors, such as age and HTT CAG triplet repeat count 7, 8, 9, 10. None of the potential biomarkers has been studied longitudinally 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Various immunoassays, ranging from sandwich-type immunoassays 2224 to time-resolved Forster resonance energy transfer (TR-FRET) based assays 25, 26 can inform on HTT levels in different sample types. However, studying HTT conformation remains a challenge and is predominantly addressed using biophysical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Successful quantification of soluble CSF mutant huntingtin was only achieved in early 2015 [83]. We used a single molecule counting (SMC) immunoassay, and a combination of HTT N-terminal-detecting 2B7 antibody and polyglutamine-binding MW1 antibody, to quantify mHTT for the first time in CSF at femtomolar sensitivity (Fig.…”
Section: Mutant Huntingtinmentioning
confidence: 99%
“…mHTT correlated with (C) disease burden score and (D) Unified Huntington's Disease Rating Scale motor score. Adapted from Wild et al [83] with the author's and publisher's permission. mice expressing human mHTT, and that the signal in CSF was correlated significantly with brain mHTT level after intracerebroventricular administration of an HTT-lowering antisense oligonucleotide.…”
Section: Mutant Huntingtinmentioning
confidence: 99%